Analysis Of Tsunami Hazard Potential On The Coast Of Bitung City, North Sulawesi - Ulus, Frangky Octavian; Mandagi, Stephanus Vianny; Sumilat, Deiske Adeliene (Sam Ratulangi University, 2025)
This thesis aims to study the tsunami hazards in the Maluku Sea region, particularly in the coastal area of Bitung, Indonesia. The research focuses on modeling and analyzing the potential tsunamis triggered by earthquake events in that region. The data used includes bathymetry, topography, coastline, and river data obtained from the Geospatial Information Agency (Badan Informasi Geospatial-BIG). The tsunami modeling process utilizes the software COMCOT (Cornell Multi-grid Coupled Tsunami). The earthquake source parameters (PusGen) used in the modeling, such as magnitude, focal depth, length of the fault plane, the width of the fault plane, dislocation of the fault plane, strike, dip, slip/rake, and modeling area, were obtained from worst-case scenarios based on PusGen's research results. The research consists of two main stages: the pre-verification stage, where data processing and tsunami modeling are conducted, and the verification stage, where field surveys are carried out to determine the coordinates for Temporary Evacuation Sites (TEP) and Final Evacuation Sites (FEP). Various equipment, such as GPS, altimeters, stopwatches, cameras, and drones, are used during the field verification. The research procedures include a literature review, data collection of topography, bathymetry, earthquake parameters, and fault mechanism. Subsequently, tsunami modeling is conducted, and hazard analysis is performed based on the model results. Tsunami hazard maps are generated to highlight high-risk areas in the coastal region of Bitung, and evacuation routes are identified to prepare the coastal community of Bitung to face potential tsunami threats. The research offers important information to assist in the development of warning systems and efficient evacuation strategies to protect the coastal community of Bitung from tsunamis' devastating impacts. Keywords: Tsunami; Bitung; coastal area; earthquake; PusGen